2006
DOI: 10.1038/sj.onc.1209342
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hRFI inhibits 5-fluorouracil-induced apoptosis in colorectal cancer cells via activation of NF-κB and upregulation of BCL-2 and BCL-XL

Abstract: Resistance to apoptosis is one of the important determinants of resistance to 5-fluorouracil (5-FU) in colorectal cancer cells. Human Ring-Finger homologous to Inhibitor of apoptosis protein type (hRFI) is a newly discovered gene that has been shown to inhibit death receptormediated apoptosis in colorectal cancer cells. However, the molecular mechanism of the inhibition of apoptosis is presently unknown. In order to investigate the molecular function of hRFI in the regulation of 5-FU-induced apoptosis in color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…Inhibition of Bcl-2 expression by siRNA transfection could significantly abolish the inhibition of GAS1 on cell survival, which is also consistent with the known role of Bcl-2 as a primary regulator of apoptosis. The phenomenon that apoptosis inhibition through up-regulating Bcl-2 correlates positively with CDDP and 5-FU resistance in various malignant tumors has been reported previously (62)(63)(64)(65)(66), which is consistent with our results. Although it has been indicated that GAS1 could inhibit apoptosis in some systems (67), many studies were supportive that GAS1 was correlated with cell cycle arrest and could act as a tumor suppressor or an inducer of cell death and apoptosis (61).…”
Section: Volume 284 • Number 39 • September 25 2009supporting
confidence: 82%
“…Inhibition of Bcl-2 expression by siRNA transfection could significantly abolish the inhibition of GAS1 on cell survival, which is also consistent with the known role of Bcl-2 as a primary regulator of apoptosis. The phenomenon that apoptosis inhibition through up-regulating Bcl-2 correlates positively with CDDP and 5-FU resistance in various malignant tumors has been reported previously (62)(63)(64)(65)(66), which is consistent with our results. Although it has been indicated that GAS1 could inhibit apoptosis in some systems (67), many studies were supportive that GAS1 was correlated with cell cycle arrest and could act as a tumor suppressor or an inducer of cell death and apoptosis (61).…”
Section: Volume 284 • Number 39 • September 25 2009supporting
confidence: 82%
“…We also examined Bcl-xL expression because Bcl-xL is regulated by Fn14 and NF-κB (6) and the expression of Bcl-xL is induced by 5-FU. Bcl-xL is also known to be upregulated in 5-FU-resistant colon cancer cells (22). As predicted, Bcl-xL was upregulated following 5-FU treatment in both cell lines (Fig.…”
Section: -Fu Treatment Upregulates the Levels Of Fn14 Mrna And Protesupporting
confidence: 49%
“…Evidence indicates that management of the mitochondrial apoptotic pathway may, at least in part, contribute to solving the problem of drug resistance. Bcl-2 and Bcl-xL block the release of cytochrome c followed by caspase-3 activation through stabilization of mitochondrial membrane integrity and subsequent regulation of the mitochondrial apoptotic pathway (18,22). Indeed, Bcl-xL is overexpressed in 5-FU-resistant cells and knock-down of Bcl-xL expression promotes sensitivity to 5-FU in colon cancer (29).…”
Section: Discussionmentioning
confidence: 99%
“…Many eVorts are being made to develop anticancer drugs that eYciently inhibit Bcl-2. Previous studies have shown that changes in Bcl-2 family are found in several chemotherapy resistance cell line (Colié et al 2009;Doudican et al 2008;Konishi et al 2006). Studies have shown that during Ara-C-based induction chemotherapy in AML patients, Bcl-2 protein levels increased signiWcantly (AndreeV et al 1999).…”
Section: Discussionmentioning
confidence: 98%